Feasibility of the A‐STEP for the assessment of exercise capacity in people with cystic fibrosis. Issue 10 (18th July 2022) - Wilson, Lisa M.; Potter, Angela; Maher, Carol; Ellis, Matthew J.; Lane, Rebecca L.; Wilson, John W.; Keating, Dominic T.; Jaberzadeh, Shapour; Button, Brenda M.
Abstract: Objectives: To evaluate feasibility of the Alfred Step Test Exercise Protocol (A‐STEP) for the assessment of exercise capacity in adults and children with cystic fibrosis (CF); in adults to test whether demographics and/or lung function correlated with exercise capacity. Methods: Adults and children with stable CF from two centres completed the A‐STEP (a recently developed incremental maximal‐effort step test). Feasibility was evaluated by: usefulness for exercise capacity assessment (measures of exercise capacity were: level reached, exercise‐induced desaturation, and achievement of at least one maximal effort criteria); safety; operational factors; time to complete; floor and/or ceiling effects. We used multiple linear regression to test whether demographics and/or lung function correlated with exercise capacity. Results: A total of 49 participants: 38 adults (18 male), percent predicted (pp) forced expiration in one second (FEV1 ) 29–109, aged 22–48 years and 11 children (6 male), ppFEV1 68–107, aged 10–15 years were included. Levels reached (mean ( SD ) [range]) were 10.2 (2.4) [6–15] (adults), 10.1 (2.5) [7–14] (children); desaturation (change between baseline and peak‐exercise SpO2 ): was 8.4 (3.8 [0–15]% (adults), 2.0 (2.0) [0–7]% (children). A total of 8 (21%) adults and no children desaturated <90% SpO2 . At least one criterion for maximal effort was reached by 33 (84%) adults and 10 (91%) children. There were no adverse events. The A‐STEP was straightforward to use and carried out by one operator. A total of 26 (68.4%) adults and 7 (63.6%) children completed the test within the recommended 8–12 min. All participants completed a minimum of 6 levels, and completed the test before the final 16th level. In adults, ppFEV1 and ppFVC correlated with the level reached ( r = 0.55; p = <0.001 and r = 0.66, p = <0.0001) and desaturation ( r = 0.55, p = <0.001 and r = 0.45, p = <0.005). Conclusion: In adults and children with stable CF, the A‐STEP was feasible, safe, and operationally easy to use for the assessment of exercise capacity, without floor or ceiling effects. In adults, lung function correlated with exercise capacity.